2011
DOI: 10.3109/00016489.2011.577447
|View full text |Cite
|
Sign up to set email alerts
|

Combined protocol for treatment of secondary effects from facial nerve palsy

Abstract: Patients who were preliminarily treated with BTX-A in the affected area showed a 2.1 improvement of score on the SunnyBrook scale (p < 0.001), with significantly better results in comparison to the non-BTX-A group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
1
28
0
3
Order By: Relevance
“…10,26 Treatment often includes botulinum toxin, massage, and stretching to reduce synkinesis and hypertonus. 20,21 Specific exercises and compensation strategies are implemented also for the correct management of problems occurring when drinking, speaking (eg. slowing speech), eating, and smiling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,26 Treatment often includes botulinum toxin, massage, and stretching to reduce synkinesis and hypertonus. 20,21 Specific exercises and compensation strategies are implemented also for the correct management of problems occurring when drinking, speaking (eg. slowing speech), eating, and smiling.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 In an attempt to prevent or reduce these residual deficits, continuous efforts have been made to identify the most effective therapeutic approaches, including medications, 17 physical therapy, 18 or a combination of both. 19-21…”
Section: Introductionmentioning
confidence: 99%
“…When used in conjunction with neuromuscular rehabilitation, botulinum toxin allows for isolation of coordinated movement patterns without the co-contraction and constraints of antagonizing muscle groups caused by synkinesis or hyperkinesis. 27,28 Both treatment modalities have been shown to be useful, particularly when used concomitantly, and have been associated with objective improvements in quality of life. 29 Despite this evidence, we found that botulinum toxin was provided to only 0.8% (296) of adults and 0.1% (3) of children within 2 years of the index date.…”
Section: Discussionmentioning
confidence: 99%
“…There are a limited number of clinical trials and research focused towards the efficacy of biofeedback therapy and BTX to treat sequelae facial nerve palsy ( 8 , 18 , 19 ). A comparison between the use of Kabat exercise or proprioceptive neuromuscular facilitation (PNF) alone and the combination of BTX and PNF with low sample size was reported in 2011 by Monini et al( 23 ). Patients graded House-Brackmann II and III were enrolled in this study and were treated by PNF and evaluated by partial FGS.…”
Section: Discussionmentioning
confidence: 99%